Analysis of Language Style in the Song Lyrics in Nadin Amizah's Album For the World, Love and Dirt: Stilistica Study - Puput Novel Pakaya; Sitti Rachmi Masie; Ellyana Hinta (Raja Zulkarnain Education Foundation, 2026)
Songs are a form of literary work that combine melody and rhythm. This study examines the figurative language and the meaning of figurative expressions found in Nadin Amizah’s album “Untuk Dunia, Cinta, dan Kotornya” (For the World, Love, and Its Filth). The purpose of this research is to: (1) describe the types of figurative language and the meanings contained in the figurative expressions used in the lyrics of Nadin Amizah’s songs in the album “Untuk Dunia, Cinta, dan Kotornya.” The method used is descriptive with a qualitative research type. The research data includes lyrics from the song album “For the World, Love, and Dirty” by Nadin Amizah. The data source of this research is the song lyrics. Data collection techniques include reading, understanding, and grouping data from the results of observation guidelines, namely figurative language style in Nadin Amizah’s song lyrics in the album “For the World, Love, and Dirty”. Data was analyzed by first selecting narratives, identifying, classifying, analyzing, and presenting the results in descriptive form. The research began with reading the data, classifying, analyzing, describing, and concluding with a summary of the results. The results of this study show that the lyrics in the album “Untuk Dunia, Cinta, dan Kotornya” contain seven types of figurative language: metaphor, simile, personification, allusion, antonomasia, sarcasm, and innuendo. Across these seven types, a total of twenty-eight lyrical excerpts were identified. The analysis of the meanings of figurative language also produced similar findings, with seven types of figurative expressions and twenty-eight lyrical excerpts containing figurative meaning.